Defending Checks and Balances in EU Member States Taking Stock of Europe's Actions - von Bogdandy, Armin; Bogdanowicz, Piotr; Canor, Iris; Grabenwarter, Christoph; Taborowski, Maciej; Schmidt, Matthias (Beiträge zum ausländischen öffentlichen Recht und Völkerrecht, 2021)
This open access book deals with Article 7 TEU measures, court proceedings, financial sanctions and the EU Rule of Law Framework to protect EU values with a particular focus on checks and balances in EU Member States. It analyses substantive standards, powers, procedures as well as the consequences and implications of the various instruments. It combines the analysis of the European level, be it the EU or the Council of Europe, with that of the national level, in particular in Hungary and Poland. The LM judgment of the European Court of Justice is made subject to detailed scrutiny.